Comparison of gross pathology inspection and 9.4 T magnetic resonance imaging in the evaluation of radiofrequency ablation lesions in the left ventricle of the swine heart - Odehnalová, Eva; Valíková, Lucia; Caluori, Guido; Kulík, Tomáš; Římalová, Veronika; Jadczyk, Tomasz; Dražanová, Eva; Pavlova, Iveta; Pešl, Martin; Kubeš, Václav; Stárek, Zdeněk (Frontiers in Physiology, 2022)
Aims: Gross pathology inspection (patho) is the gold standard for the morphological evaluation of focal myocardial pathology. Examination with 9.4 T magnetic resonance imaging (MRI) is a new method for very accurate display of myocardial pathology. The aim of this study was to compare these two methods for the evaluation of radiofrequency (RF) ablation lesion dimensions in swine heart tissue during animal experiment. Methods: Ten pigs underwent radiofrequency ablations in the left ventricle during animal experiment After animal euthanasia, hearts were explanted, flushed with ice-cold cardioplegic solution to relax the whole myocardium, fixed in 10% formaldehyde and scanned with a 9.4 T magnetic resonance system. Anatomical images were processed using ImageJ software. Subsequently, the hearts were sliced, slices were photographed and measured in ImageJ software. Different dimensions and volumes were compared. Results: The results of both methods were statistically compared. Depth by MRI was 8.771 ± 2.595 mm and by patho 9.008 ± 2.823 mm; p= 0.198. Width was 10.802 ± 2.724 mm by MRI and 11.125 ± 2.801 mm by patho; p=0.049. Estuary was 2.006 ± 0.867 mm by MRI and 2.001 ± 0.872 mm by patho; p=0.953. The depth at the maximum diameter was 4.734 ± 1.532 mm on MRI and 4.783 ± 1.648 mm from the patho; p=0.858. The volumes of the lesions calculated using a formula were 315.973 ± 257.673 mm3 for MRI and 355.726 ± 255.860 mm3 for patho; p=0.104. Volume directly measured from MRI with the “point-by-point” method was 671.702 ± 362.299 mm3. Conclusion: Measurements obtained from gross pathology inspection and MRI are fully comparable. The advantage of MRI is that it is a non-destructive method enabling repeated measurements in all possible anatomical projections. In addition, MRI allows more precise volume measurement using the direct “point-by-point” method.